Tax havens : how globalization really works - Palan, Ronen, 1957- (Cornell studies in money., 2010)
"In Tax Havens, Ronen Palan, Richard Murphy, and Christian Chavagneux provide an up-to-date evaluation of the role and function of tax havens in the global financial system--their history, inner workings, impact, extent, and enforcement."--Page [iv] of cover.